2020
DOI: 10.3390/plants9111475
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Pratylenchus (Nematoda: Pratylenchidae) in Israel: From Taxonomy to Control Practices

Abstract: Due to Israel’s successful agricultural production and diverse climatic conditions, plant-parasitic nematodes are flourishing. The occurrence of new, previously unidentified species in Israel or of suggested new species worldwide is a consequence of the continuous withdrawal of efficient nematicides. Among plant-parasitic nematodes, migratory endoparasitic species of the genus Pratylenchus are widely distributed in vegetable and crop fields in Israel and are associated with major reductions in quality and yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The populations analyzed in this research were identified through the use of morphological and morphometric characteristic. PCA separated the species identified in this study from others that are morphologically and morphometrically similar, showing the importance of morphological and morphometric data, in addition to multivariate statistical analysis for the identification of species of the genus Pratylenchus (Castillo and Vovlas, 2007;Múnera et al, 2009;Singh et al, 2018;Qing et al, 2019;Riascos-Oritiz et al, 2019).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The populations analyzed in this research were identified through the use of morphological and morphometric characteristic. PCA separated the species identified in this study from others that are morphologically and morphometrically similar, showing the importance of morphological and morphometric data, in addition to multivariate statistical analysis for the identification of species of the genus Pratylenchus (Castillo and Vovlas, 2007;Múnera et al, 2009;Singh et al, 2018;Qing et al, 2019;Riascos-Oritiz et al, 2019).…”
Section: Discussionmentioning
confidence: 61%
“…Species of Pratylenchus are difficult to separate from each other, due to their similarity in morphometrics and morphology, although the genus is easily recognizable (Castillo and Vovlas, 2007). However, based on an integrative taxonomy approach, including morphological, morphometric, and molecular characterization, the populations obtained in this study associated with Musa spp.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In Brazil, P. coffeae infests about 1% of citrus nurseries and orchards [ 43 ], while it has a major trend in Florida, USA [ 44 ]. Other RLN species were described to be prominent such as P. vulnus and P. neglectus in Israel [ 45 ], and P. vulnus and P. coffeae in Morocco [ 7 ]. These species can significantly reduce root weight, which translated into significant yield losses [ 4 ].…”
Section: Discussionmentioning
confidence: 99%